Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.32479/ijeep.7469
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This investigation analyses the influence of real activities earnings management on firm performance of the energy listed firms on Vietnam's stock market. Our data collection constitutes 29 energy companies on Vietnam stock markets (HNX and HOSE) in the period from 2010 to 2016. We used regression analysis in accordance with panel data, namely fixed effects model and random effects model. The results determine that real activity earnings management positively impacts on firm performance. This implies that incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
10
0
3
Order By: Relevance
“…On the other hand, the results of many research have shown that profit management leads to the improved financial condition of companies (Sayari and Omri 2017;Khuong et al 2019;Abbas and Ayub 2019;Mostafa 2020;Zhang and Ayisi 2020;Nobakht and Acar 2021). For example, Sayari and Omri (2017) saw a positive relationship between discretionary accruals and Tunisian firms' stocks, indicating that discretionary accruals allow Tunisian investors to construct their stocks portfolios optimally.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results of many research have shown that profit management leads to the improved financial condition of companies (Sayari and Omri 2017;Khuong et al 2019;Abbas and Ayub 2019;Mostafa 2020;Zhang and Ayisi 2020;Nobakht and Acar 2021). For example, Sayari and Omri (2017) saw a positive relationship between discretionary accruals and Tunisian firms' stocks, indicating that discretionary accruals allow Tunisian investors to construct their stocks portfolios optimally.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
“…So far, some research has been done on the impact of earnings management on corporate financial performance (Tabassum et al 2013;Gill et al 2013;Mehrani and Noruzi 2015;Rodriguez-Ariza et al 2016;Sayari and Omri 2017;Okafor et al 2018;Darmawan et al 2019;Khuong et al 2019;Abbas and Ayub 2019;Mostafa 2020;Zhang and Ayisi 2020;Dakhlallh et al 2020;Nobakht and Acar 2021), while some others have focused on the relationship between related party transactions and firm value (Cheung et al 2006;Xiao and Zhao 2009;Kohlbeck and Mayhew 2010;Pozzoli and Venuti 2014;Tambunan et al 2017;Fazli 2019;Hendratama and Barokah 2020;Ashrafi et al 2020), each of which has had different results for various reasons. This gap is fully felt in the research literature to simultaneously examine the effects of earnings management as well as related party transactions on corporate financial performance during a financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Masih terdapat banyak perusahaan yang terpengaruh masalah ini demi nilai kinerja. Pada saat yang sama, Khuong et al (2019) menjelaskan laba berpengertian realitas penting universal yang menentukan status keuangan dan kesehatan semua perusahaan asuransi.…”
Section: Pendahuluanunclassified
“…Menurut Mahrani & Soewarno (2018) pengaruh manajemen laba berbasis akrual bersignifikan negatif terhadap kinerja perusahaan. Sedangkan hasil penelitian Khuong et al (2019) menunjukkan bahwa manajemen laba berbasis riil menghasilkan hubungan bersignifikan positif pada kinerja perusahaan. Pada waktu yang sama, Adryanti (2019) menemukan manajemen laba basis akrual dan riil berpengaruh signifikan positif pada kinerja perusahaan.…”
Section: Kinerja Perusahaanunclassified
See 1 more Smart Citation